Association of Plasma Glucose to Potassium Ratio and Mortality After Aneurysmal Subarachnoid Hemorrhage - Jung, Hyun Min; Paik, Jin Hui; Kim, Sin Young; Hong, Dae Young (Frontiers in Neurology, 2021)
Objectives: Hyperglycemia and hypokalemia are common problems in patients with aneurysmal subarachnoid hemorrhage (aSAH). The aim of this study was to determine whether the plasma glucose to potassium ratio (GPR) predicts mortality due to aSAH. Methods: We prospectively recruited aSAH patients and healthy controls between March 2007 and May 2017. Clinical outcomes included mortality and poor outcome (modified Rankin scale score of 3 to 6) after three months. Multivariable analysis was used to determine the association between plasma GPR and 3-month mortality in aSAH patients. Results: A total of 553 patients were recruited, and the mortality rate was 11%. The GPR was significantly elevated in aSAH patients compared with controls, in patients with a poor outcome than with a good outcome and in nonsurvivals than in survivals. Multivariable analysis showed that the plasma GPR was an independent factor associated with 3-month mortality. The area under the curve of the GPR was 0.747 in predicting 3-month mortality. Conclusion: The plasma GPR on admission has potential as a predictor of 3-month mortality in patients with aSAH..